2005
DOI: 10.7589/0090-3558-41.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ecologic Basis for Extreme Susceptibility of Pallas' Cats (Otocolobus Manul) to Fatal Toxoplasmosis

Abstract: Recent efforts by North American zoos to establish a genetically viable captive population of Pallas' cats (Otocolobus manul) have been compromised by high newborn mortality (ϳ60%), primarily because of toxoplasmosis. The basis for this extreme susceptibility to toxoplasmosis is unknown. In the present study, the general health status of wild Pallas' cats in Mongolia was evaluated, including assessment of basal hematologic parameters and fecal corticoid metabolite concentrations. The prevalence of exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…First, a small percentage (13%) of Pallas' cats had detectable antibodies to Toxoplasma (Table 2), similar to results of Brown et al (2002) on Mongolian Pallas' cats, where 2 of 15 cats (13%) were positive. Thus, our results confirm the low frequency of T. gondii in wild Pallas' cats in different habitats.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…First, a small percentage (13%) of Pallas' cats had detectable antibodies to Toxoplasma (Table 2), similar to results of Brown et al (2002) on Mongolian Pallas' cats, where 2 of 15 cats (13%) were positive. Thus, our results confirm the low frequency of T. gondii in wild Pallas' cats in different habitats.…”
Section: Discussionsupporting
confidence: 69%
“…Captive breeding of Pallas' cats has been successful; however, there are no persistent captive populations because kitten survival is low (,40%;Swanson 1999;Kenny et al 2002) because of susceptibility to Toxoplasma gondii (Dubey et al 1988;Basso et al 2005). Brown et al (2002) showed that prevalence of antibodies to T. gondii was 13% in wild cats in Mongolia, but 100% in cats in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, wild Pallas' cats have minimal opportunity for exposure to T. gondii in their isolated natural habitat in Central Asia and, typically, do not become infected with this parasite until being brought into captivity. This could explain their extreme susceptibility to toxoplasmosis [132], which could threaten conservation programs devoted to this species [133]. Although no specific case has been documented in the wild, T. gondii may threaten local wild-living populations, for example when new human settlements come in contact with isolated endangered populations.…”
Section: The Dynamics Of T Gondii In Wildlife In Temperate Climatesmentioning
confidence: 99%
“…Given the Pallas' cat's habitat of uplands, steppe and semi-desert regions, human population density in its distribution range is very low. While in the Pallas' cats Russian distribution range, sheepherders and cattle farms keep domestic cats as companion animals, this is not the case in other parts of its range (in Mongolia for example; Brown et al, 2005). Given that the Pallas' cats themselves only occur at low densities, it appears unlikely that the parasite generally has a high prevalence in this newly discovered defi nitive host.…”
Section: Discussionmentioning
confidence: 95%
“…Given the decline of wild Pallas' cats, knowledge of the general health status of wild population may be important in a conservation context. For example, while toxoplasmosis leads to high mortality rates of new-borns in captive populations, exposure to Toxoplasma gondii appears to be minimal in the wild (Brown et al, 2005). Here, we present the fi rst record of a T. cati infestation observed in a Pallas' cat sampled in Kyrgyzstan.…”
Section: Introductionmentioning
confidence: 83%